2016
DOI: 10.4103/0972-0707.173205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of composite insertion technique on gap formation

Abstract: Aim:To compare newer bulk-fill composites with an incrementally filled composite for adaptability and subsequent gap formation at the pulpal floor.Materials and Methods:Class I cavities were prepared in 60 intact molars, with a shallow depression in the center of the pulpal floor. The samples were divided into four groups (n = 15), according to the material used; smart dentine replacement (SDR), SonicFill, Ever X Flow and Z350 XT, restored to a depth of 4 mm. Following thermocycling, samples were sectioned buc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…In addition, Benetti et al, 30 when using an LVDT and an electron microscope, did not observe any difference in polymerization shrinkage, gap formation, and polymerization depth between SFS and TBF in class II cavities. However, Kapoor et al 10 found better adaptability and lower gap formation in the pulp wall when bulk fill RCs were used compared with conventional RCs, but the analysis was made by SEM, which may raise some doubts about final gap formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Benetti et al, 30 when using an LVDT and an electron microscope, did not observe any difference in polymerization shrinkage, gap formation, and polymerization depth between SFS and TBF in class II cavities. However, Kapoor et al 10 found better adaptability and lower gap formation in the pulp wall when bulk fill RCs were used compared with conventional RCs, but the analysis was made by SEM, which may raise some doubts about final gap formation.…”
Section: Discussionmentioning
confidence: 99%
“…9 In recent years, bulk fill RCs have been proposed to decrease polymerization shrinkage and gap formation in the pulp wall, 10 inserted in a single thick layer (4-5 mm). 11,12 RCs seem to have low polymerization shrinkage and a small percentage of voids, 13 besides large clinical acceptance, 14,15 since they simplify the restorative process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bulk-fill restoratives have become the material of choice, particularly in deep cavities, as they reduce the number of steps required for the application, by filling the cavity in a single increment of 4 to 5 mm, and decrease the chair side time 32) . The increased Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of the bulk-fill composite resin material would be to reduce interfacial gap formation of incremental technique and clinical steps by filling the cavity in a "single" increment leading to a reduced porosity and a uniform consistency for the restoration, further reducing the clinical time taken and cost factor of the patient. 4 Depending on the viscosity of resin material, four types of bulk-fill resins are available in the market which includes, smart dentin replacement (SDR) (Dentsply, DeTrey, Konstanz, Germany), EverX-flow (GC Europe), QuiXfil (Dentsply, UK), Venus Bulk-Fill (Heraeus Kulzer, USA), Tetric EvoCeram BulkFill (Ivoclar Vivadent, Amherst, NY), X-tra fil (Voco, USA), SonicFill (Kerr, SybronEndo, USA), and fiber-reinforced bulk-fill composite, EQUIA Forte (GC Europe).…”
Section: Introductionmentioning
confidence: 99%